2016
DOI: 10.1111/iej.12683
|View full text |Cite
|
Sign up to set email alerts
|

Human dental pulp cells response to mineral trioxide aggregate (MTA) and MTA Plus: cytotoxicity and gene expression analysis

Abstract: MTA and MTA Plus were noncytotoxic, increased mineralization processes in vitro and induced the expression of osteogenic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 40 publications
3
39
1
Order By: Relevance
“…All of the tested materials maintained cell viability and proliferation, and no evidence of damage to the cell membrane and DNA was found. Corroborating with our findings, previous studies have shown that ProRoot MTA, MTA-Angelus and PC were not cytotoxic, allowing a cell viability of 70% or higher, as required by the ISO guidelines (4,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…All of the tested materials maintained cell viability and proliferation, and no evidence of damage to the cell membrane and DNA was found. Corroborating with our findings, previous studies have shown that ProRoot MTA, MTA-Angelus and PC were not cytotoxic, allowing a cell viability of 70% or higher, as required by the ISO guidelines (4,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 91%
“…Production of OCN by osteoblastic cells in contact with MTA has been demonstrated in vitro (Tani‐Ishii et al ). In addition, MTA has been shown to induce the expression of the BMP‐2 and OCN osteogenic markers in dental pulp cells (Rodrigues et al ) and both MTA and Biodentine™ induced BMP‐2 expression in osteogenic cells and were considered adequate materials to stimulate the mineralization by osteoblastic cells (Rodrigues et al ). BSP is also involved in the formation of the mineralized matrix, and the expression of this protein is highly specific for mineralized tissues including bone, cartilage, dentine and cementum (Tani‐Ishii et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Four in vitro studies addressing the bio activity and cytotoxicity of the materials used as cervical barriers were selected. [6][7][8][9] Regarding the publication years and journals, one article from 2014 was found in the Journal of Endodontics, 6 one article from 2015 in the Dental Materials, 9 and two articles from 2017 in the International Endodontic Journal 7 and the Journal of Medical Sciences. 8 The findings are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2,3,10,18 Among pulp revascularization stages, this study assessed the use of different materials used as cervical barrier. Of the materials evaluated in this study, articles were found using white and gray MTA, [6][7][8][9][10][11][12][13][14][15][16] Biodentine, 9,14,15,18 EndoSequence, 14,15 TheraCal, 9 and the Calcium-Enriched Mixture (CEM). 4,8,17 The materials used in cervical sealing act as physical barrier, protecting the clot and preventing possible recontamination.…”
Section: Discussionmentioning
confidence: 99%